Rola Lorda Kanclerza jako stróża praworządności w brytyjskim systemie ustrojowym - Oślizło, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article presents one of the most iconic and prestigious offices in Great Britain – The Office of Lord Chancellor. The majority of the author’s analysis is centred around the radical constitutional reform which had affected the office of Lord Chancellor throughout the last two decades. Author’s primary focus is on the topic of appointing the candidates for the office of Lord Chancellor. Finally, there is an examination of the subject of the rule of law, which seems to be the most important constitutional principle in Great Britain.
Keywords: Lord Chancellor; Great Offices of State; House of Lords; Constitutional Reform Act; constitutional principles; Cabinet; rule of law